Evaluation of synergistic antidiabetic activity in vitro and in vivo of Taraxacum officinale (L.) Weber Ex F.H.Wigg and Momordica charantia L. dual herbal combination - Perumal, Nithiyaa (2021)
Diabetes type 2 is the most common type of diabetes, which accounts for 90% of most diabetes cases. Many commercial drugs were used to treat this disease, however these drugs come with adverse side effects and eventually all of them fail to restore the normal glycemic control in patients. Therefore, the search for a more effective antidiabetic agent preferably from dietary source, which is economical and non-toxic or less toxic was considered. Many herbal plants have been found to show multiple antidiabetic activities when used alone or in combination. Therefore, the dual herbal combination of Taraxacum officinale (L.) Weber ex F.H.Wigg and Momordica charantia L. crude extracts were chosen in this study owing to the numerous antidiabetic compounds present in both plant extracts. Basically, the dried and ground samples of T. officinale (whole plant) and M. charantia (fruit) were extracted with Soxhlet apparatus using a range of non-polar solvents (petroleum ether, chloroform and ethyl acetate) and polar solvents (acetone, ethanol and water) separately. The extracts were screened for Total Phenolic Content (TPC), Total Flavonoid Content (TFC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. The antidiabetic properties of the extracts were assessed via glucose uptake assay using L6 muscle cells, dipeptidyl peptidase-4 (DPP-4), α-amylase and α-glucosidase inhibition activity via enzyme-substrate based reaction assays as well as in vivo acute toxicology, oral glucose tolerance test (OGTT) and a 28-day antidiabetic study in a streptozotocin-nicotinamide (STZ-NA) induced diabetic rat model. Based on this study, the polar extracts of both T. officinale and M. charantia recorded higher phytochemical contents and increased DPPH scavenging activity compared to the non-polar extracts. The ethanolic extracts of both T. officinale and M. charantia showed optimum antidiabetic properties (ANOVA, p<0.05). Therefore, both these ethanolic extracts were combined in the ratio of 1:1 to further assess it synergistic antidiabetic activity. The dual herbal combination proved to exert better antidiabetic properties compared to the single extracts of T. officinale and M. charantia since there was a significant (ANOVA, p<0.05) increase in percentage inhibition of DPP-4, α-amylase and α-glucosidase enzymes. The percentage inhibition of DPP-4 of the dual herbal combination was 81.34±0.07, compared to 43.69±0.56 and 14.62±0.81 percent as recorded by both T. officinale and M. charantia respectively. The IC50 values recorded by the dual herbal combination towards α-amylase and α-glucosidase enzymes were 2.77±0.16 and 28.82±0.67 mg/ml respectively, which was significantly (ANOVA, p<0.05) the lowest value in comparison to the single extracts. However, the dual herbal combination was noted to show a moderate glucose uptake activity, since there was no significant difference (ANOVA, p>0.05) compared to the single extract of T. officinale but a significantly (ANOVA, p<0.05) lower glucose uptake activity when compared to the single extract of M. charantia. As for the in vivo study, the dual herbal combination was proved non-toxic as none of the test animals showed any symptoms of poisoning or toxicity. The dual herbal combination tested in vivo on STZ-NA induced diabetic rat model showed blood glucose lowering activity of the test sample at 250 mg/kg body weight (b.w) were comparable to that of Glibenclamide (1 mg/kg b.w), where the blood glucose level was significantly (ANOVA, p<0.05) restored within 60 minutes post glucose administration during OGTT. Besides, at the end of the 28-days antidiabetic study, it was shown that the antihyperglycemic activity of the dual herbal combination at 250 mg/kg b.w was also comparable to all three positive drugs, namely, Glibenclamide (1 mg/kg), Metformin (50 mg/kg) and Sitagliptin (10 mg/kg), because, under these treatments, the hyperglycemic condition of the test animals was not aggravated throughout the entire four weeks of study. The presence of various polyphenol compounds such as caffeic acid and taraxacin in T. officinale and charantin and polypeptide-p in M. charantia have contributed to the various antidiabetic properties in the respective ethanolic extracts, hence showing an improved antidiabetic activity upon combination both in vitro and in vivo. The combined synergistic activities of these two plants in displaying antidiabetic activities proves to be a potential dual herbal combination which is safe and less toxic to manage Type 2 Diabetes Mellitus.